Molecular Insights into Signalling Pathways and Therapeutic Monitoring of Chronic Low-grade Inflammation-associated Obesity - Nidhi Singh; Avijit Mazumder; Priyanka Bansal (Current Signal Transduction Therapy, 2026)
Introduction: Obesity has emerged as a major global public health concern. It is a multifactorial condition encompassing genetic, environmental, socioeconomic, and psychosocial factors. This narrative review aims to highlight the key pathophysiological processes associated with chronic low-grade inflammation (CLGI) in obesity. Methods: Data collection was performed using the PubMed, Scopus, Web of Science, and Google Scholar databases, using the search terms “chronic low-grade inflammation”, “pathophysiology of obesity,” and “metabolic syndrome” to obtain relevant articles. Results: The pathophysiological sequence underlying CLGI-associated obesity begins with adipose tissue expansion, during which hypertrophic adipocytes trigger cellular stress manifested as hypoxia and ER stress, accompanied by the release of damage-associated molecular patterns (DAMPs). This initiates a vicious cycle involving the recruitment of macrophages and their proinflammatory M1 polarization, with activation of inflammatory pathways, such as NF-κB and the NLRP3 inflammasome. These changes further contribute to the induction of systemic insulin resistance and metabolic dysregulation. Discussion: Both tissue and systemic biomarkers are valuable in identifying and monitoring CLGI-associated obesity. Treatment approaches ranging from pharmacological agents and bariatric surgery to dietary modifications, exercise, and microbiome-based therapies are relevant for managing inflammation and metabolic health. Conclusion: In conclusion, strategic immunotargeting of CLGI through context-specific interventions can serve as an innovative therapeutic strategy to treat CLGI-associated obesity and potentially mitigate the resulting comorbid metabolic burden. Future efforts should prioritize the development of multi-marker approaches within precision medicine frameworks to enable more individualized care for patients with CLGI-associated obesity.